MULTIPLE INTELLIGENCE-BASED ACTIVITIES: ITS EFFECTS ON ESSAY WRITING SKILLS - Agrissto Bintang Aji Pradana; Tri Pujiani; Meiliana Nurfitriani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Writing English essay requires complex abilities, such as critical thinking and academic writing and students often find it difficult. Beside they are using foreign language, the activities did not accommodate their personal traits and learning styles. This study was an attempt to find out the profile of students’ Multiple Intelligence (MI) and the effects of MI based activities on their essay writing skills. This experimental research was conducted in Universitas Muhammadiyah Magelang in 2020. Then 60 out of 160 fourth semester students of Elementary School Teacher Education Department were assigned as the sample. The primary data were obtained through tests supported by observation and interview. The data were assumed to be normal and homogenous. Based on the statistical analysis of Independent t-test, Sig. (2-tailed) 0.900 > 0.05. The average scores of posttest of Experimental Group also found greater than the one of control group. These concluded that MI based activities affected students’ essay writing skills. The results could be a beneficial reference in promoting students’ essay writing skills in higher education.